How to Change the Travellers' Mobility Behaviours? - Examples of Mobility Plans - Katarzyna Nosal (Communications - Scientific letters of the University of Zilina, 2009)
The paper presents a mobility management concept as well as gives examples of mobility plans which are fundamental instruments of mobility management. A mobility plan includes activities for the promotion of sustainable mobility modes: bikes, public transport, walking trips and new means of private car usage (carpooling, carsharing systems). It also consists of solutions which realize an idea of sustainable transportation. Mobility plan activities allow to fulfill travellers’ mobility needs and shape their mobility behaviours.